Decreased Myocardial Fibrinolytic Activity Following Temporary Ischaemia and Reperfusion - Cherry, George W; Opie, L. H (Thrombosis and Haemostasis, 1975)
The effect of temporary myocardial ischaemia (x 52 mins) and reperfusion (x 23 hrs 8 mins) on myocardial tissue fibrinolysis and 125I fibrinogen incorporation into fibrin was investigated in nine baboons.Fibrinolytic activity was reduced by 54% in the endocardium of the ischaemic reperfused myocardium and the 125I fibrinogen activity was elevated by 480%.The reduction in myocardial fibrinolytic activity following ischaemia and reperfusion may be due to endothelial damage.